Transformations of the Right to Health Care Content, and its Connection with the Right to Biotechnology - M. Khurmatullina, Alsu; R. Amirova, Rimma (International Journal of Engineering and Technology, 2018)
The paper updates the concept and the content of the constitutional right of a person and citizen. The concept of "biotechnology" is emphasized. The possibility of applying the methods of patent analysis to study the state of biotechnology is discussed.The results of the study are based on the use of the following methods: a universal dialectical method of scientific knowledge, as well as general scientific methods based on it (description, analysis, synthesis, induction, deduction, comparison, analogy, generalization) and specific scientific methods (comparative legal, system-structural and formal legal).Â Â